2014
DOI: 10.1161/circresaha.115.304517
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modification at Notch Responsive Promoters Blunts Efficacy of Inducing Notch Pathway Reactivation After Myocardial Infarction

Abstract: Rationale:The Notch pathway plays a key role in stimulating mammalian cardiomyocyte proliferation during development and in the early postnatal life; in adult zebrafish, reactivation of this pathway is also essential to drive cardiac regeneration after injury.Objective: We wanted to assess efficacy of Notch pathway stimulation in neonatal and adult hearts as a means to induce cardiac regeneration after myocardial infarction in mice. Methods and Results:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 63 publications
3
54
0
Order By: Relevance
“…These studies have identified the acquisition of an epigenetic signature during cardiomyocyte maturation ( [60]. This indicates that adult cardiomyocytes may need to be epigenetically reset for efficient cell cycle re-induction before regeneration can occur (Fig.…”
Section: Dynamic Changes In the Epigenome During Cardiomyocyte Differmentioning
confidence: 99%
“…These studies have identified the acquisition of an epigenetic signature during cardiomyocyte maturation ( [60]. This indicates that adult cardiomyocytes may need to be epigenetically reset for efficient cell cycle re-induction before regeneration can occur (Fig.…”
Section: Dynamic Changes In the Epigenome During Cardiomyocyte Differmentioning
confidence: 99%
“…While the study design does not permit exclusion of a possible contribution of systemic effects of 5azato the observed cardiac phenotype, the in vivo findings are consistent with two recent in vitro studies in cultured neonatal rat cardiomyocytes , which suggested that 5azainduces cardiomyocyte proliferation and inhibits endothelin-induced cardiomyocyte binucleation (Felician et al, 2014b;Kou et al, 2010;Paradis et al, 2014). These striking effects of 5azaon cardiomyocyte binucleation are particularly interesting given that hypomethylating agents such as 5azaare commonly used as anti-cancer drugs and have anti-proliferative effects in other cell types.…”
Section: Discussionsupporting
confidence: 81%
“…There is growing interest in the potential for induction of adult cardiomyocyte proliferation as a strategy for promoting cardiac regeneration following MI and a recent study suggests that epigenetics plays a key role in this process. Notch stimulation was shown to induce proliferation of neonatal cardiomyocytes, but not adult cardiomyocytes (Felician et al, 2014b). Felician et al demonstrated that the accumulation of repressive histone marks (H3K27me3) and DNA methylation marks at the promoters of Notch-responsive signalling effectors during neonatal development prevented Notch ligands from re-inducing proliferation in adult cardiomyocytes (Felician et al, 2014b).…”
Section: Global Epigenetic Modificationmentioning
confidence: 99%
See 2 more Smart Citations